PENGEMBANGAN PROFESI BAGI GURU MADRASAH ALIYAH MELALUI DIKLAT PKG DAN PKB DI BKD JAKARTA - Umi Maisyaroh As (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2020)
This study aims to determine the ability to understand the concept of professional development and the skills to compile the scientific publication of PKG and PKB Substantive Technical Training participants for Madrasah Aliyah teachers at the Jakarta Religious Education and Training Center in 2019. The method used in this research is a survey method with a qualitative approach. Data collection techniques used tests, rubrics and structured interviews. The data analysis technique used is descriptive qualitative with three stages, namely data reduction, display and verification. The results of this study indicate that, through PKG & PKB Substantive Technical training for Madrasah Aliyah teachers can increase understanding of the concept of teacher professional development and improve teacher skills in compiling Scientific Publications.